UPAYA MENINGKATKAN HASIL BELAJAR MELALUI PENDEKATAN PICTURE AND PICTURE PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN - Salwa Awa Iqlima; Heri Hidayat; Heny Mulyani; Sely Rosmiati; Tia Rahmawati (Bhineka Tunggal Ika: Kajian Teori dan Praktik Pendidikan PKn, 2020)
Abstract: In the learning process every teacher must know must know the models in teaching, so students can follow the learning well. One learning model that can be done is to use picture and picture model that can develop students’s abilities in obtaining material. In the learning process picture and picture the teacher shows the pictures to students in an sorted / paired into a logical sequence. These images are the main factors in the learning process from beginning to end. So students can focus and rull well. The learning has the characteristics of active, innovative, creative and fun. In conducting research in class 2 SDN 267 Griya Bumi Antapani we conducted 2 studies, namely the control class and the experimental class. In entering the control class we only use the lecture method while in the experimental class we use a picture and picture model with image media. From the result of the data that we obtained showed that the control class did not understand the material provided by the teacher while the experimental class understood the material provided by the teacher and could apply it in everyday life.